Linking Sedimentological and Spatial Analysis to Assess the Impact of the Forestry Industry on Soil Loss: The Case of Lanalhue Basin, Chile - Alaniz-Baeza, A (Elsevier B.V., 2021)
Soil loss has become one of the main problems associated with global change over the last decades. New assessments are needed in order to improve our understanding of the real impacts of human productive activities on the natural dynamics linked to erosion in lake basins. We analyzed the recent and historical dynamics of soil loss in a coastal lake basin of central Chile (Lanalhue lake), evaluating land use impacts and proposing management changes to control erosion and restore the soil. We implemented two approaches: A) Using a high-resolution sedimentological proxy and a high-accuracy chronology of cores to determine the sediment accumulation rate, organic/inorganic matter and granulometry for the last 120 years; and B) applying the Universal Soil Loss Equation to estimate erosion of soil from hills during the last 32 years, considering a combination of satellite, climate, soil, and land-cover topographic data. We found that the sedimentation rates, as well as the concentration of organic matter in lake sediments, were relatively constant from 1900 to 1950; after that, they experienced a significant increase. The same pattern of rapid increase was found for sand content. We found that erosion during the last 30 years has been high and constant, especially in bare soil (mainly clear-cutting areas) and exotic forest plantations. Erosion has been significantly higher within exotic forest plantations, reaching 31 ton/ha/yr in clear-cutting areas. Three industrial forestry companies accounted for 61.5% of the basin surface where urgent erosion control is needed. Our findings support the indication that industrial forestry is the main activity affecting erosion dynamics in the basin; secondarily, earthquakes have been important modulators of the sediment dynamics in Lanalhue during these last 120 years. © 2021 Elsevier B.V.